Sustainable biomass of pirarucu juveniles in small volume net cages - Cavero, Bruno Adan Sagratzki; Filho, Manoel Pereira; Roubach, Rodrigo; Ituassú, Daniel Rabello; Gandra, André Lima; Crescêncio, Roger (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to estimate the sustainable biomass of pirarucu Arapaima gigas (Cuvier, 1829) juveniles kept in small volume net cages. During 200 days four 1-m3 net cages were stocked with 21 fish/cage and had an initial total biomass of 0.84±0.14 kg (21 fish/cage). The net cages were placed in a 50-m2 pond with constant water flow. Conditioning factor, feed conversion, specific growth rate and gain showed that the sustainable biomass of pirarucu juveniles for intensive rearing in 1-m3 net cages was approximately 29 kg. Fish length at the end of the trial, in relation to the reduced net cage space, was a limiting factor to obtain good biological indices.